Ships from hell Japanese war crimes on the high seas - Lamont-Brown, Raymond (Sutton Publishing, 2002)
More than 140,000 Caucasian PoWs fell to the Japanese Imperial Army and Navy in the Second World War. Many of these men were shipped to the Japanese main islands for slave labour, in seaborne transports crammed with PoWs in their airless holds, and stricken with disease. Countless hundreds of Allied troops and civilians died at sea. Sick, starved, suffocated, tortured and massacred when they became a nuisance, or killed when the unmarked transports were bombed by the Allies, the prisoners experienced unbelievable horrors. Raymond Lamont-Brown's chilling account also covers the barbaric actions of the Imperial Japanese Navy in the wake of its attacks on Allied merchant shipping, from the ramming of lifeboats, attacks on hospital ships, the machine-gunning of survivors in the water, to the beheading of naval captives. Whereas many other accounts of Japanese atrocities have concentrated on the fate of PoWs on land, the author has researched original Japanese records and drawn on eyewitness accounts to write this frightening account of Japanese barbarity against defenceless prisoners of war at sea.